UNRAVELING THE ROLE OF WORK ENGAGEMENT IN THE RELATIONSHIP BETWEEN WORK–LIFE BALANCE TO EMPLOYEE PERFORMANCE - Hery Verianto The (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study investigates the mediating role of work engagement within the unique, target-driven environment of a microfinance institution in West Kalimantan. Ultimately, these findings aim to resolve existing empirical contradictions, enrich human resource management theory, and provide strategic, evidence-based guidance for maximizing productivity through well-being initiatives in the microfinancial sector. Research Methodology: A quantitative, descriptive–causal design was employed. The analysis included tests of validity and reliability, classical assumption testing, path analysis, and the Sobel test to evaluate the mediating effect of work engagement. A census sampling technique was applied, involving 50 employees, and the data were analyzed using  SPSS version 23. Results: The findings reveal that both work–life balance and work engagement partially have positive and significant effects on employee performance. Moreover, the direct effect of work–life balance on performance is stronger than its indirect effect through work engagement, indicating that work engagement has the capacity to mediate though the direct effect plays more importance role. Conclusion: Work-life balance improves work engagement and employee performance, with work engagement serving as a partial mediator. However, the direct influence of work-life balance remains the strongest pathway for enhancing productivity. Limitations: This study is limited by its cross-sectional design, quantitative survey approach, and focus on a single institution. Future studies should apply longitudinal and mixed-method designs across broader organizational and regional contexts. Contributions: Theoretically, this study extends Conservation of Resources theory in the microfinance sector by confirming work engagement as a partial mediator. Practically, it recommends HR strategies focused on workload control, clear work-life boundaries, and well-being programs to reduce burnout and sustain employee performance.